(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the intricate relationship between phonetics and word formation in the English language, focusing on key processes such as derivation, compounding, blending, acronyms, and conversion. It highlights how these processes not only create new words but also influence their phonetic characteristics, including stress patterns, sound alterations, and pronunciation variations. For instance, it explains how the addition of affixes in derivation can change stress placement (e.g., "happy" to "happiness") and how compounds typically feature primary stress on the first element (e.g., "toothbrush"). The article also discusses the fluid nature of blends and the phonetic transformations in acronyms and initialisms. By examining these word-formation processes, the article emphasizes the dynamic evolution of English and its adaptability, illustrating how phonetic rules shape language development and usage. Overall, the piece provides valuable insights into the interplay between sound and meaning in English vocabulary expansion